P1_8 Bright Nosed and Bushy Tailed - Tranter, Jemima; Roberts, Kieran; Holt, Nicholas; Murphy, Jeremy (Physics Special Topics, 2020)
Rudolph the Red-Nosed Reindeer has a very shiny nose and if you ever saw it, you might even say it glowed. The purpose of this paper is to find out how much energy, in the form of carrots, Rudolph would need to help guide Santa's sleigh through thick clouds and fog with his nose. By comparing his nose to a 40W incandescent light bulb, we conclude that approximately 151 carrots would be required to provide power for the 12-hour night shift.